Wheel-rail creep force model for predicting water induced low adhesion phenomena. (May 2017) - Trummer, G.; Buckley-Johnstone, L.E.; Voltr, P.; Meierhofer, A.; Lewis, R.; Six, K.
Abstract: A computationally efficient engineering model to predict adhesion in rolling contact in the presence of water is presented which may be implemented in multibody dynamics software or in braking models to study train performance and braking strategies. This model has been developed in a project funded by the Rail Safety and Standards Board (RSSB) and Network Rail. It is referred to as the water-induced low adhesion creep force (WILAC) model. The model covers a wide range of conditions from dry over damp to wet. Special emphasis is put on little amounts of water which can cause low adhesion without any oil or grease. Such conditions may be encountered in humid weather or at the onset of rain. The model is parameterised based on experimental results from a tram wheel test rig. Adhesion values as low as 0.06 are observed at high creep with only wear debris and little water present in the contact. The model results also agree with experimental data from locomotive tests in dry and wet conditions.